2021
DOI: 10.1016/j.scitotenv.2020.143195
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring discharge in a tidal river using water level observations: Application to the Saigon River, Vietnam

Abstract: The hydrological dynamics of the Saigon River is ruled by a complex combination of factors, which need to be disentangled to prevent and limit risks of flooding and salt intrusion. In particular, the Saigon water discharge is highly influenced by tidal cycles with a relatively low net discharge. This study proposes a low-cost technique to estimate river discharge at high frequency (every 10 minutes in this study). It is based on a stage-fall-discharge (SFD) rating curve adapted from the general Manning Strickl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…4). In contrast to the rainy season, the residual water discharge in Saigon River was very low (30 m 3 s − 1 ) during the dry season (Camenen et al 2021). The residence time of the water body in this urban section of Saigon River was estimated to be around two months (Nguyen et al 2021).…”
Section: Spatial Effect On Phytoplankton Communitiesmentioning
confidence: 93%
See 1 more Smart Citation
“…4). In contrast to the rainy season, the residual water discharge in Saigon River was very low (30 m 3 s − 1 ) during the dry season (Camenen et al 2021). The residence time of the water body in this urban section of Saigon River was estimated to be around two months (Nguyen et al 2021).…”
Section: Spatial Effect On Phytoplankton Communitiesmentioning
confidence: 93%
“…The ow direction of the Saigon River is predominantly driven by the asymmetric semi-diurnal tides that lead to the ow current inversion twice a day, roughly in the range from − 1500 to + 1500 m 3 s − 1 (Camenen et al 2021). The region falls within a tropical monsoon climate with two distinct seasons.…”
Section: Study Areamentioning
confidence: 99%
“…The high polluted loads regularly lead to an excess of nutrients and intense periods of anoxia, especially during the dry season . There have been several studies in recent years showing the risk of eutrophication in this estuary, especially in the dry season because of low flushing capacity (Camenen et al, 2020;Strady et al, 2017). In addition, the research results of showed that there was no significant difference between water quality variables in rainy season and dry season (except chlorophyll a).…”
Section: Introductionmentioning
confidence: 87%
“…Hydrological data (water level, velocity, discharge) were measured monthly at 10 stations along the Saigon and Dongnai rivers by the CEM. Once a month, the hydrological monitoring stations track the evolution of water level and velocity over 24 h (2 tidal cycles) to calculate the net water discharge by removing the influence of tidal fluctuations in the Saigon River Estuary (Camenen et al, 2020).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation